Older Adult Homicide: Investigating Case, Victim and Perpetrator Characteristics in a National Sample from England and Wales - Storey, Jennifer E; Rogers, Michaela M; Hohn, Richard E (The British journal of social work, 2024)
Abstract Older adult homicide (OAH) is the most severe, yet understudied, form of older adult abuse. This study examined the case, victim and perpetrator characteristics of OAH. A secondary analysis of national data from England and Wales (2008–2019) was conducted where cases of non-stranger OAH (victims aged sixty years and over) were compared to adult homicide (victims aged eighteen to fifty-nine years) at the case, victim (n = 3,274) and perpetrator (n = 2,763) levels. Logistic regression models used to identify characteristics that were OAH risk factors, showed only a slight increase in predictive power but high accuracy in classifying adult homicide cases. Nevertheless, some risk factors known to be predictors of older adult abuse were significant predictors of OAH (e.g. living with the perpetrator, the perpetrator’s mental state). Implications for research, policy and practice are discussed. This study set out to develop new knowledge around the severe and understudied issue of older adult homicide (OAH). To do this, we reviewed the records of all UK homicides between 2008 and 2019 held by the UK Home Office where victims and perpetrators were known to each other. We examined characteristics related to the case and victim in 3,274 records and characteristics of the perpetrators in 2,763 records. To draw conclusions about OAH, we compared cases involving victims aged sixty and over to cases with victims aged eighteen to fifty-nine. Characteristics were compared across age groups using logistic regression to determine if certain characteristics predicted OAH. Some characteristics were predictive of OAH (e.g. living with the perpetrator, the perpetrator’s mental state) and are also known to predict older adult abuse. However, the analysis showed that the characteristics currently included in the dataset were more predictive of adult homicide than OAH. This suggests that additional national data should be collected which is more relevant to OAH and that older adult abuse risk factors may be helpful in that regard.